The Development of Creative Abilities as a Factor of the Social Maturity of Adolescents - Emishyants, Olga; Trofimov, Andrii; Hrys, Antonina; Pavliuk, Mariia; Shopsha, Olena; Tereshchuk, Angelina; Polishchuk, Svetlana (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
The article considers the concept of the social maturity of adolescents in the context of the development of creative abilities. The relationships of social maturity with socialization, social creativity and innovative thinking of adolescents are researched. It is found that girls are more likely to move from the previous to the next level of social maturity. It is found that with age, the ability to social creativity develops. There is a connection between the level of social creativity and the levels of social autonomy, social morality and social activity of adolescents.